2021
DOI: 10.1021/acs.inorgchem.1c01716
|View full text |Cite
|
Sign up to set email alerts
|

Lattice-Matched CoP/CoS2 Heterostructure Cocatalyst to Boost Photocatalytic H2 Generation

Abstract: Transition-metal phosphides and sulfides are considered as promising cocatalysts for the photocatalytic hydrogen evolution reaction (HER), and the cocatalytic effect can be improved by directed heterostructure engineering. In this study, a novel lattice-matched CoP/CoS 2 heterostructure having a nanosheet morphology was developed as an HER cocatalyst and integrated in situ onto graphitic carbon nitride (g-C 3 N 4 ) nanosheets via a successive phosphorization and vulcanization route. First-principles density fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The excellent electronic conductivity of Mo 2 N, Co–Mo 2 N and Cu–Mo 2 N endows them with the promoted photogenerated charge migration as high-performance cocatalysts for the HER. 27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The excellent electronic conductivity of Mo 2 N, Co–Mo 2 N and Cu–Mo 2 N endows them with the promoted photogenerated charge migration as high-performance cocatalysts for the HER. 27…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the DOS intensities of doped samples were enhanced by metal-atom doping. The excellent electronic conductivity of Mo 2 N, Co-Mo 2 N and Cu-Mo 2 N endows them with the promoted photogenerated charge migration as high-performance cocatalysts for the HER 27. XRD characterization and Fourier transform infrared spectroscopy (FT-IR) were performed over the prepared Mo 2 N/ g-C 3 N 4 , Cu-Mo 2 N/g-C 3 N 4 and Co-Mo 2 N/g-C 3 N 4 to study their crystal structure and surface functional groups.…”
mentioning
confidence: 99%
“…A single semiconductor as a photocatalyst possesses numerous disadvantages such as a large band gap, narrow absorption spectral response, high electron–hole recombination rate, and difficult carrier separation, which make it difficult to exhibit a high photocatalytic activity for hydrogen production. Designing multiple semiconductors to form heterojunctions can compensate for the shortcomings of pure semiconductors and create synergistic effects in semiconductor composites by combining the excellent properties of each semiconductor. The compound semiconductor has superior photocatalytic activity, which greatly enhances the rate and amount of hydrogen evolution. Semiconductor–semiconductor heterojunctions are often classified as cross-gap (Type I), interleaved-gap (Type II), and gap (Type III). , The more effective type II heterojunctions are mainly p–n-type heterojunctions, which results in forming an internal electric field at the interface, thus promoting the effective separation of photogenerated electrons and holes. The n–n (p–p)-type heterojunctions drive the transfer of photogenerated carriers based on the valence and CB positions of the catalyst itself. It has been found that Z-type heterojunctions could boost light trapping ability by the means of inhibiting photogenerated electron and hole recombination and promoting surface catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor photocatalysis has been a hot topic for decades since the first report on photocatalytic water splitting for TiO 2 , 1 and many efforts have been made to understand the photocatalytic mechanism, develop new catalysts, and improve catalytic efficiency, respectively. [2][3][4][5][6][7] Photocatalysis becomes more and more important both in environmental protection through photo-driven degradation of organic pollutants and in solving the energy crisis by photocatalytic hydrogen generation from water. 8,9 To date, a great number of semiconductors have been studied as well as their combinations to form composites, which are beneficial for enhancing the light harvesting ability or decreasing the recombination rate of photo-excitons, thus achieving a high efficiency.…”
Section: Introductionmentioning
confidence: 99%